Hypercalcemia remains an adverse prognostic factor for newly diagnosed multiple myeloma patients in the era of novel antimyeloma therapies. (26th September 2017) - Zagouri, Flora; Kastritis, Efstathios; Zomas, Athanasios; Terpos, Evangelos; Katodritou, Eirini; Symeonidis, Argiris; Delimpasi, Sosana; Pouli, Anastasia; Vassilakopoulos, Theodoros P.; Michalis, Eurydiki; Giannouli, Stavroula; Kartasis, Zafiris; et al.
Abstract: Objectives: To evaluate the prognostic impact of hypercalcemia in newly diagnosed patients with symptomatic multiple myeloma (MM), especially after the incorporation of new agents. Methods: we analyzed the outcomes of newly diagnosed patients with symptomatic myeloma included in the database of the Greek Myeloma Study Group for the prognostic effect of the presence of hypercalcemia (defined as corrected serum calcium ≥11 mg/dL) at diagnosis. Results: Among 2129 consecutive patients with symptomatic MM, 19.5% presented with hypercalcemia at the time of diagnosis. The presence of hypercalcemia was associated with anemia, thrombocytopenia, lower estimated glomerular filtration rate (eGFR), advanced ISS stage, and presence of lytic lesions. Hypercalcemia was more common in patients with high‐risk cytogenetics and was associated with inferior survival across different time periods, age groups, and primary treatments. Hypercalcemia was also associated with a twofold increase in the risk of early death. In patients without available FISH, hypercalcemia could substitute for the presence of high‐risk cytogenetics and identify patients with worse prognosis along with ISS stage and elevated serum LDH. Conclusion: Hypercalcemia remains a poor prognostic feature in the era of novel agents despite the improvement in the outcomes of patients who present with elevated calcium.